Shoulder abduction fatiguability. Issue 4 (April 1987) - Nicklin, J; Karni, Y; Wiles, C M
Abstract : Shoulder abduction fatiguability has been measured using a hand held myometer in normal subjects and patients with peripheral neuromuscular diseases. An index of fatiguability was based on the decline in force over a series of ten maximum voluntary contractions performed in under a minute. The technique was repeatable and well tolerated. Patients with myasthenia, mitochondrial myopathy and motor neuron disease tended to show excess fatiguability independent of muscle strength. Serial measurements demonstrated alterations in fatiguability but not necessarily strength, associated with changes in symptoms.